2006
DOI: 10.1287/isre.1060.0107
|View full text |Cite
|
Sign up to set email alerts
|

Research Note: The Influence of Recommendations and Consumer Reviews on Evaluations of Websites

Abstract: R ecommendations and consumer reviews are universally acknowledged as significant features of a businessto-consumer website. However, because of the well-documented obstacles to measuring the causal impact of these artifacts, there is still a lack of empirical evidence demonstrating their influence on two important outcome variables in the shopping context: perceived usefulness and social presence. To test the existence of a causal link between information technology (IT)-enabled support for the provision of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
194
0
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 430 publications
(232 citation statements)
references
References 37 publications
6
194
0
6
Order By: Relevance
“…Recommendations help users manage the overwhelming amount of information and create a better understanding of the key features of a service [56], which supports more careful, contrasted evaluations of an e-service prior to continuance decisions. Especially for difficult evaluations such as e-services, information about important others is valuable, because the recipient knows that peers are unlikely to expose him or her to any undue harm.…”
Section: Recommendations From Public Administrations and Interpersonamentioning
confidence: 99%
“…Recommendations help users manage the overwhelming amount of information and create a better understanding of the key features of a service [56], which supports more careful, contrasted evaluations of an e-service prior to continuance decisions. Especially for difficult evaluations such as e-services, information about important others is valuable, because the recipient knows that peers are unlikely to expose him or her to any undue harm.…”
Section: Recommendations From Public Administrations and Interpersonamentioning
confidence: 99%
“…Person-to-person interactivity in the form of blog can significantly influence users' attitude toward the Website (Thorson & Rodgers 2006). In addition, online consumer review system is considered as one of the most powerful channels to generate online word-of-mouth (Dellarocas 2003), and the presence of consumer reviews on Website has been shown to improve consumer perception of the usefulness and social presence of the Website (Kumar & Benbasat 2006). Reviews have the potential to attract consumer visits, increase the time spent on the site ("stickiness"), and create a sense of community among frequent shoppers (Mudambi & Schuff 2010).…”
Section: Impact Of Person Interactivity On E-retailers' Operational Pmentioning
confidence: 99%
“…NA (Kumar and Benbasat, 2006) Social presence refers to the degree to which a medium allows an individual to establish a personal connection with others (Short et al, 1976). (Gefen and Straub, 2004) Customer review and recommendation Source Definition of SP Measures IT Artifacts (Lee et al, 2006) A psychological state in which virtual (paraauthentic or artificial) actors are experienced as actual social actors in either sensory or nonsensory ways.…”
Section: Appendix Ii: Unidimensional Conceptualization Of Social Presmentioning
confidence: 99%